Digital Disruption: The New York Times Asia-Pacific Writing Competition 2018 - New York Times (Institutional Knowledge at Singapore Management University, 2019)
This is a yearly writing competition organised by International New York Times (NYT). This year’s topic is “Digital Disruption” and SMU’s social sciences student Victoria Ivory Birrell was the winner in the University category. See her essay: Ignore the Fluff, Technology hasn’t failed us and here’s why